KEDUDUKAN ALAT BUKTI ELEKTRONIK DALAM PERKARA DI PENGADILAN AGAMA - Yusuf Wibisono (Institut Agama Islam Ngawi, 2022)
Abstract: Human activities that have started using electronics have an effect on the condition of the evidence, namely the electronic device itself. The problem that arises as a problem in the verification process is the emergence of a variety of electronic transactions which then gave birth to certain electronic transactions, which on the other hand are evidence that can be used in the future. Even though the procedural law has not been proven through electronic evidence. If this phenomenon is ruled out, then evidence as an effort to provide certainty and truth about the existence of certain events will be hampered. Each piece of evidence has its own strength of evidence which has been determined by law. The type of research used in compiling this journal is library research by reviewing and researching various documents or literature, such as: books, fiqh books, laws and regulations, jurisprudence that are related to this research. The results of this study are how to prove by using Electronic Information evidence in a case in a religious court the same as submitting written or letter evidence, which is submitted in a civil trial, namely in the form of a copy or photocopy of the written evidence, and must be matched. with the original first. Electronic evidence brought to trial must be verified. If the evidence produced by the electronic object is true, then the electronic evidence must be classified as evidence. Keywords: Position, Electronic Evidence, Religious Court